Potential of integrated multitrophic aquaculture to make prawn farming sustainable in Bangladesh - Alam, Md. Mehedi; Jørgensen, Niels O. G.; Bass, David; Santi, Morena; Nielsen, Max; Rahman, Md. Asadur; Hasan, Neaz A.; Bablee, Alif Layla; Bashar, Abul; Hossain, Md. Ismail; Hansen, Lars Hestbjerg; Haque, Mohammad Mahfujul (Frontiers in Sustainable Food Systems, 2024)
Farmed freshwater prawn (Macrobrachium rosenbergii) and black tiger shrimp (Penaeus monodon) comprise a significant portion of Bangladesh’s seafood exports, raising concerns about their environmental impacts. Freshwater prawn farms, which require a relatively high amount of feed supply, release 1.0 MT CO2-equivalents/year, equating to 18.8 kg CO2e/MT prawn, contributing significantly to global warming and climate change risks. Integrated Multi-Trophic Aquaculture (IMTA) offers an alternative farming method to conventional prawn farming systems, as it minimizes greenhouse gas (GHG) emissions and climate change impacts. Systematically reviewing 112 scientific articles on IMTA, this article offers recommendations for adopting IMTA to promote sustainable freshwater prawn farming in Bangladesh. IMTA is undergoing extensive experimentation and practice in many parts of the world, offering economic benefits, social acceptability, and environmental sustainability. In addition to native prawn species, various indigenous organic extractive freshwater mollusks, and inorganic extractive plants are available which can seamlessly be used to tailor the IMTA system. Extractive organisms, including aquatic mollusks and plants within prawn farms, can capture blue carbon effectively lowering GHG emissions and helping mitigate climate change impacts. Aquatic mollusks offer feed for fish and livestock, while aquatic plants serve as a dual food source and contribute to compost manure production for crop fields. Research on IMTA in Bangladesh was primarily experimented on finfish in freshwater ponds, with the absence of studies on IMTA in prawn farms. This necessitates conducting research at the prawn farmer level to understand the production of extractive aquatic mollusk and plants alongside prawn in the prawn-producing regions of southwestern Bangladesh.